Pro ASP.NET MVC framework. - Sanderson, Steven, ....- (Berkeley : Apress, 2009)
The ASP.NET MVC Framework is the latest evolution of Microsoft's ASP.NET web platform. It introduces a radically new high-productivity programming model that promotes cleaner code architecture, test-driven development, and powerful extensibility, combined with all the benefits of ASP.NET 3.5. An integral benefit of this book is that the core Model-View-Controller architectural concepts are not simply explained or discussed in isolation, but demonstrated in action. You'll work through an extended tutorial to create a working e-commerce web application that combines ASP.NET MVC with the latest C# 3.5 language features and unit-testing best practices. By gaining this invaluable, practical experience, you can discover MVCs strengths and weaknesses for yourself-and put your best learned theory into practice.